Full gate voltage range Lambert-function based methodology for FDSOI MOSFET parameter extraction. (September 2015) - Karatsori, T.A.; Theodorou, C.G.; Ioannidis, E.G.; Haendler, S.; Josse, E.; Dimitriadis, C.A.; Ghibaudo, G.
Highlights: Full gate voltage range MOSFET parameter extraction method. Extraction of 5 electrical FDSOI parameters from Id – Vg in linear region. Good comparison with parameters extracted from Y-function method. Verification over a wide range of channel lengths on FDSOI devices. Abstract: A new full gate voltage range methodology using a Lambert W function based inversion charge model, for extracting the electrical parameters in FDSOI nano-MOSFET devices, has been developed. Split capacitance–voltage measurements carried out on 14 nm technology FDSOI devices show that the inversion charge variation with gate voltage can be well described by a Lambert W function. Based on the drain current equation in the linear region including the inversion charge described by the Lambert function of gate voltage and the standard mobility equation enables five electrical MOSFET parameters to be extracted from experimental Id – Vg measurements (ideality factor, threshold voltage, low field mobility, first and second order mobility attenuation factors). The extracted parameters were compared with those extracted by the well-known Y-function in strong inversion region. The present methodology for extracting the electrical MOSFET parameters was verified over a wide range of channel lengths on nano-scale FDSOI devices, demonstrating its simplicity, accuracy and robustness.